2006
DOI: 10.1542/peds.2005-0378
|View full text |Cite|
|
Sign up to set email alerts
|

Acute and Sustained Effects of Lucinactant Versus Poractant-α on Pulmonary Gas Exchange and Mechanics in Premature Lambs With Respiratory Distress Syndrome

Abstract: Among preterm lambs with severe RDS, lucinactant produced improvements in gas exchange and lung mechanics similar to those observed with a porcine-derived surfactant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 52 publications
0
28
1
1
Order By: Relevance
“…This comparative study was carried out using 14 premature Latxa lambs delivered at 133 d of gestation (term = 145 d), it having been shown that there is severe pulmonary SF deficiency in lambs of this breed at this gestational age (29,30). Mean body weight of the lambs at birth was 3.1 ± 0.4 kg.…”
Section: Methodsmentioning
confidence: 99%
“…This comparative study was carried out using 14 premature Latxa lambs delivered at 133 d of gestation (term = 145 d), it having been shown that there is severe pulmonary SF deficiency in lambs of this breed at this gestational age (29,30). Mean body weight of the lambs at birth was 3.1 ± 0.4 kg.…”
Section: Methodsmentioning
confidence: 99%
“…These preparations showed promising results in preclinical models of lung disease (20,21) and some of them were tested in clinical trials (19,(22)(23)(24). However, increased improvement of lung function by synthetic surfactants containing both SP-B and SP-C analogues, over that with a single surfactant protein, have previously been suggested (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…The effi cacy of different surfactant preparations is diffi cult to compare in many studies using small groups of animals with large individual responses. In a recent study using 6 premature lambs with a gestational age of 135 days (term 145 days) in each treatment group, the conclusion was stated that lucinactant (Surfaxin) and poractantalfa (Curosurf) produced similar improvements in gas exchange and lung mechanics even though 2 of the 6 animals did not respond to Surfaxin and the mean value of PaO 2 in this group was about 35% lower and the mean airway pressures higher than those for the Curosurf-treated lambs [23] . With small studies such as this, statistically signifi cant differences in treatment effi cacy will be virtually impossible to demonstrate.…”
Section: Physiological Effectsmentioning
confidence: 98%